A high-ductility thin-layer repair concrete and preparation method thereof

By using refiring magnesium oxide and potassium dihydrogen phosphate components such as potassium magnesium phosphate cement, polyvinyl alcohol fiber and metakaolin in thin-layer repair materials, combined with retarding base and step-by-step stirring technology, the existing materials have been solved. The problem of shelling and fragmentation in harsh environments improves compressive, flexural and bonding strength, and enhances frost resistance.

CN118812234BActive Publication Date: 2024-12-13SHANDONG IRON GECKO BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411308387.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-13
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The existing thin-layer repair materials are prone to shelling and fragmentation in harsh climates, resulting in repair failure and poor bonding strength.

Method used

Potassium magnesium phosphate cement concrete composed of refired magnesium oxide and potassium dihydrogen phosphate, polyvinyl alcohol fiber and metakaolin clay are added to slow down the hydration reaction through retarding base, improve bonding strength and freezing resistance, and through steps Agitation improves fiber dispersion and clamping force.

Benefits of technology

It significantly improves the compressive, flexural strength and bonding strength of the repair material, reduces the cracking probability of the repair layer, enhances the freeze-thaw resistance, delays crack propagation, and improves the repair effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005132382070000111
    Figure GDA0005132382070000111
  • Figure GDA0005132382070000121
    Figure GDA0005132382070000121
  • Figure GDA0005132382070000131
    Figure GDA0005132382070000131
Patent Text Reader

Abstract

The present invention relates to a high-ductility thin-layer repair concrete and a preparation method thereof, and relates to the technical field of building materials, wherein the weight proportions of the antibacterial enamel material composition include: 35-40 parts of dead-burned magnesium oxide, 5-15 parts of potassium dihydrogen phosphate, 5-20 parts of borax, 15-40 parts of metakaolin, 20-55 parts of slow-setting base material, and 0.5-5 parts of polyvinyl alcohol fiber, wherein the slow-setting base material is at least one of fly ash and slag. The present invention can improve the compression and flexural properties of the high-ductility thin-layer repair concrete, and also improve the bonding performance of the concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a high-ductility thin-layer repair concrete and a preparation method thereof. Background Art

[0002] As one of the main forms of highway pavement in my country, cement concrete pavement is widely used in expressways, national and provincial trunk roads, municipal roads, etc. However, under the influence of vehicle loads and environmental factors, cement concrete pavement is prone to a certain degree of damage and disease in the early stage of use or after a period of use. These diseases not only affect the appearance and cleanliness of the concrete pavement, but also affect the safe passage of traffic and people's travel safety.

[0003] At present, a Chinese invention patent application with publication number CN116177968A and publication date May 30, 2023 proposes an ultra-high performance concrete and preparation method for thin-layer repair and reinforcement of cracked tunnel linings, which discloses a high-ductility pavement thin layer rapid repair material, including the following raw materials in proportion by weight: 100 to 450 parts of compound cement, 100 to 450 parts of machine-made sand, 100 to 400 parts of mineral micropowder, 10 to 30 parts of compound expansion agent, 6 to 25 parts of redispersible latex powder, 6 to 15 parts of special fiber, and 1 to 3 parts of F10 water reducer.

[0004] The optimized addition of special fibers gives this material high ductility, high crack resistance and high damage resistance.

[0005] In addition, a Chinese invention patent application with publication number CN115724636A and publication date March 3, 2023 proposes an ultra-high performance concrete for thin-layer repair and reinforcement of cracked tunnel lining and a preparation method, which discloses an ultra-high performance concrete for thin-layer repair and reinforcement of cracked tunnel lining, comprising the following components by weight: 624-780 parts of cement, 52-130 parts of silica fume, 208-286 parts of limestone powder, 954-1032 parts of river sand, 234-312 parts of steel fiber, 7.20-7.32 parts of water reducer, 5.2-10.4 parts of pure acrylic-acrylic composite emulsion, and 202-208 parts of water; wherein: polymer composite emulsion: obtained by compounding and evenly mixing pure acrylic emulsion and acrylic emulsion in a mass ratio of 6:4.

[0006] The addition of polymer composite emulsion can improve the flexural strength of the ultra-high performance concrete matrix and thin layer specimens. The higher the flexural strength, the better the toughness.

[0007] Regarding the above technical solution, although this type of material has the characteristics of high ductility and high flexural strength, its bonding strength is poor. This type of material is prone to peeling and breaking under harsh climatic conditions, which often causes the repair to fail. Summary of the invention

[0008] In order to reduce the situation where concrete peeling and cracking result in repair failure, the present invention provides a high-ductility thin-layer repair concrete and a preparation method thereof.

[0009] In the first aspect, the present invention provides a high-ductility thin-layer repair concrete, which adopts the following technical solution:

[0010] A high-ductility thin-layer repair concrete comprises, by weight, 35-40 parts of dead-burned magnesium oxide, 5-15 parts of potassium dihydrogen phosphate, 5-20 parts of borax, 15-40 parts of metakaolin, 20-55 parts of retarding base material, and 0.5-5 parts of polyvinyl alcohol fiber, wherein the retarding base material is at least one of fly ash and slag.

[0011] By adopting the above technical solution, the potassium magnesium phosphate cement concrete composed of dead-burned magnesium oxide and potassium dihydrogen phosphate has the characteristics of high strength, high bonding strength and a thermal expansion coefficient similar to that of ordinary concrete. In addition, when the temperature difference on the concrete surface changes greatly, when the repair layer is formed, the repair layer and the original concrete layer can expand synchronously, thereby reducing the probability of cracking of the repair layer.

[0012] Polyvinyl alcohol fiber has high tensile strength and elastic modulus close to that of ordinary cement concrete. As a reinforcing and toughening component, it can effectively play a bridging role in concrete, making the composite material have strain hardening properties. When concrete is subjected to bending load, when cracks appear and begin to expand, the bridging effect of the fiber transmits the crack expansion force to the surrounding uncracked areas, delaying the further expansion of the cracks, thereby improving the flexural strength of the concrete. However, when the fiber is poorly dispersed and agglomerated in the matrix concrete, the irregular orientation of the fiber destroys this consistency, and the flexural strength decreases.

[0013] At this time, the addition of metakaolin improves the plastic viscosity of the mixture and the uniformity of the dispersion of polyvinyl alcohol fibers, thereby significantly improving the uniaxial tensile strain of high-ductility cement-based composite materials. At the same time, the reaction heat of potassium magnesium phosphate cement concrete excites the active alumina component in the metakaolin, which reacts with phosphate to form aluminum phosphate cementitious substances, which has the effect of filling the gaps in the cement. At the same time, it improves the microstructure and increases the density of the cement, which is beneficial to the improvement of the early and later strength and durability of the cement. Such a complete and dense crystal structure prevents the entry of water from the external environment, thereby improving the anti-freeze and thaw performance. The viscous cementitious substances are attached to the surface of the cement particles, which increases the bonding strength and reduces the failure of repairs caused by concrete peeling and fragmentation.

[0014] The acidic environment provided by potassium dihydrogen phosphate causes the surface of the polyvinyl alcohol fiber to oxidize and coarsen the polyvinyl alcohol fiber, significantly increasing its surface roughness, thereby improving the bonding performance of the two. As the hydration age of potassium magnesium phosphate cement increases, struvite crystals are generated on the surface of the polyvinyl alcohol fiber and coated on the polyvinyl alcohol fiber, thereby enhancing the clamping force between the struvite crystals and the polyvinyl alcohol fiber.

[0015] However, since potassium magnesium phosphate cement concrete sets too fast, it is not conducive to construction operations and may damage construction tools. Borax, a retarder, is added to delay the formation and setting of hydration products.

[0016] The slow-setting base material is a filler that fills pores or cracks to improve the voids in the cement slurry, enhance the compressive properties, and improve the pore structure, density and water resistance of potassium magnesium phosphate cement.

[0017] Optionally, the ratio of the dead-burned magnesium oxide to potassium dihydrogen phosphate is 2.8-3.2:1.

[0018] By adopting the above technical solution, when the ratio of dead-burned magnesium oxide to potassium dihydrogen phosphate is about 2.8-3.2:1, the pH value is appropriate, and sufficient hydration products can be generated. The generated hydration products can more fully wrap the magnesium oxide particles, further improving the compressive strength.

[0019] Optionally, the weight proportion of the metakaolin is 20-35 parts.

[0020] By adopting the above technical solution, kaolin is not easy to reduce the fluidity of potassium magnesium phosphate cement, and at the same time it can generate sufficient reaction heat, and the amount of hydrate generated during the same period is high, which has a good effect of improving the strength, durability and bonding strength of potassium magnesium phosphate cement.

[0021] Optionally, the weight proportion of the polyvinyl alcohol fiber is 0.8-1.5 parts.

[0022] By adopting the above technical solution, the amount of polyvinyl alcohol fiber is not easy to reduce the fluidity of potassium magnesium phosphate cement, and the cement has good fluidity.

[0023] Optionally, the length of the polyvinyl alcohol fiber is 5-8 mm.

[0024] By adopting the above technical solution, the agglomeration effect of the polyvinyl alcohol fiber is smaller, which will reduce the amount of voids generated inside the concrete, enhance the reinforcement effect of the fiber, and have a better reinforcement effect.

[0025] Optionally, the weight proportions of the retarding base material are 15-40 parts of fly ash and 5-15 parts of slag.

[0026] By adopting the above technical solution, the heat released by the early hydration reaction is appropriate, so that the amount of hydration products is sufficient, and the compressive and flexural strengths of the potassium magnesium phosphate cement composite material are further improved.

[0027] Optionally, the high-ductility thin-layer repair concrete composition further includes 3 to 8 parts of a calcium enhancer, wherein the calcium enhancer is at least one of light calcium powder and calcium oxide.

[0028] Or, the fly ash is 10-25 parts of high-calcium fly ash, and the content of calcium oxide in the high-calcium fly ash is 30%-40%.

[0029] By adopting the above technical solution, as the reaction proceeds, potassium dihydrogen phosphate is gradually consumed, the pH value of the slurry increases, the dissolution rate of magnesium oxide decreases, and Ca 2+ Will replace Mg 2+ The PO4 that was not completely reacted in the early stage 3- A local reaction occurs, producing H + , H + The presence of accelerates the dissolution of dead-burned magnesia, induces the late hydration of potassium magnesium phosphate cement, and increases its compressive strength.

[0030] Preferably, the calcium increasing agent for the high-ductility thin-layer repair concrete is lightweight calcium powder.

[0031] By adopting the above technical solution, the addition of lightweight calcium powder produces a synergistic effect with kaolin and retarding base material, which has an air entraining effect. Therefore, without adding air entraining agent, the air content of the mixture reaches 5-8%, thereby greatly improving the antifreeze performance.

[0032] In a second aspect, the present invention provides a method for preparing a high-ductility thin-layer repair concrete, which adopts the following technical solution:

[0033] A method for preparing a high-ductility thin-layer repair concrete comprises the following steps:

[0034] (1) adding the dead-burned magnesium oxide, potassium dihydrogen phosphate, borax, metakaolin, and polyvinyl alcohol fiber described in the first aspect into a mixer and stirring for 3-4 minutes at a speed of 140 r / min to form a solid gelling component;

[0035] (2) adding water, wherein the ratio of the solid gelling component to water is 1:0.1-0.2, stirring for 1-2 minutes at a speed of 140 r / min, and gradually adding a slow-setting base material;

[0036] (3) Stir rapidly for 1-2 minutes at a speed of 280 r / min.

[0037] By adopting the above technical scheme, step (1) first increases the uniformity of mixing of the components, and at the same time, the irregular shape of the kaolin particles improves the uniformity of dispersion of the polyvinyl alcohol fiber, which is convenient for subsequent reactions; step (2) adds water and gradually adds a retarding base material, which can provide a higher acidic environment at the beginning, coarsen the polyvinyl alcohol fiber, and significantly increase the surface roughness of the added polyvinyl alcohol fiber, thereby improving the bonding performance of the two; step (3) quickly stirs to allow the components to react fully.

[0038] Optionally, the borax is qualified dried borax, and the condition for qualified drying of the borax is: each drying is at 60-70° C., the drying time is ensured to be between 30-40 hours, and the final three-time mass reduction rate of the borax is less than 0.1%.

[0039] By adopting the above technical solution and using dried and qualified borax, the water content in the borax can be reduced. In the subsequent synthetic materials, the "wall hanging" phenomenon can be alleviated to ensure construction efficiency.

[0040] Optionally, the ratio of the solid gelling component to water is 1:0.15-0.2.

[0041] By adopting the above technical solution, the hardening speed is moderate, which is more conducive to construction. The appropriate amount of mixing water is not easy to evaporate to form pores, which reduces the porosity of the material, improves the structural density, and enables the material to be fully hydrated, thereby improving the strength of potassium magnesium phosphate cement.

[0042] Optionally, in step (1), the amount of polyvinyl alcohol fiber added is 30-50% of the total amount of polyvinyl alcohol fiber added, and the remaining polyvinyl alcohol fiber is added to water to wet it;

[0043] In step (2), the water added is water soaked with polyvinyl alcohol fibers, and the ratio of the solid gelling component to water is 1:0.1-0.15.

[0044] By adopting the above technical scheme, by improving step (1) and step (2), the metakaolin particles can be uniformly dispersed in the polyvinyl alcohol fibers, and the remaining wet polyvinyl alcohol fibers can be used to slowly replenish water for the concrete, thereby reducing the dissolution rate of potassium dihydrogen phosphate and slowing down the hydration heat generated by the dead-burned magnesium oxide and potassium dihydrogen phosphate to generate a sufficient amount of hydration products. The potassium dihydrogen phosphate first contacts and dissolves with the wetted polyvinyl alcohol fibers, further improving the acidic environment near the polyvinyl alcohol fibers, making the polyvinyl alcohol fibers more fully coarsened, and making it easier to generate struvite crystals on the surface of the polyvinyl alcohol fibers and coat them on the polyvinyl alcohol fibers, thereby enhancing the clamping force between the struvite crystals and the polyvinyl alcohol fibers.

[0045] In summary, the present invention includes at least one of the following beneficial technical effects:

[0046] 1. Potassium magnesium phosphate cement concrete composed of reburned magnesium oxide and potassium dihydrogen phosphate has the characteristics of high strength, high bonding strength and thermal expansion coefficient similar to that of ordinary concrete. In addition, when the temperature difference of the concrete surface changes greatly, the repair layer and the original concrete layer can expand synchronously when the repair layer is formed, reducing the probability of cracking of the repair layer;

[0047] 2. The addition of kaolin improves the plastic viscosity of the mixture and the uniformity of the dispersion of polyvinyl alcohol fibers, thereby significantly improving the uniaxial tensile strain of high-ductility cement-based composite materials. It has the effect of filling the gaps in the cement, while improving the microstructure and increasing the density of the cement, which is beneficial to the improvement of the early and later strength and durability of the cement. It also has a sticky gelling substance that adheres to the surface of the cement particles, increasing the bonding strength.

[0048] 3. The addition of kaolin and retarding base material enables potassium magnesium phosphate cement to form a complete and dense crystal structure to prevent the entry of water from the external environment, thereby improving the freeze-thaw resistance. At the same time, the addition of lightweight calcium powder and the synergistic effect of kaolin and retarding base material will also greatly improve the anti-freeze performance.

[0049] 4. By adding polyvinyl alcohol fibers in steps, the hydration heat generated by dead-burned magnesium oxide and potassium dihydrogen phosphate is slowed down to generate sufficient hydration products, thereby increasing the compressive strength and making the polyvinyl alcohol fibers coarsened more fully, making it easier to generate struvite crystals on the surface of the polyvinyl alcohol fibers and coat them on the polyvinyl alcohol fibers, thereby enhancing the clamping force between the struvite crystals and the polyvinyl alcohol fibers. DETAILED DESCRIPTION

[0050] The present invention is further described in detail below with reference to the embodiments.

[0051] Example 1: This example discloses a high-ductility thin-layer repair concrete, which includes, by weight, 36 parts of dead-burned magnesium oxide, 12 parts of potassium dihydrogen phosphate, 10 parts of dried and qualified borax, 25 parts of metakaolin, 25 parts of fly ash, 10 parts of slag, and 1.2 parts of polyvinyl alcohol fiber.

[0052] The preparation method is as follows,

[0053] (1) adding the above-mentioned dead-burned magnesium oxide, potassium dihydrogen phosphate, dried qualified borax, metakaolin, and polyvinyl alcohol fiber into a mixer, wherein the conditions for the qualified drying of the borax are: drying at 60-70° C. each time, ensuring that the drying time is between 30-40 hours, and the final three-time weight reduction rate of the borax is less than 0.1%; stirring for 3 minutes at a speed of 140 r / min to form a solid gelling component;

[0054] (2) adding water, wherein the ratio of the solid gelling component to water is 1:0.16, stirring for 1.5 minutes at a speed of 140 r / min, and gradually adding a slow-setting base material;

[0055] (3) Rapid stirring for 2 minutes at a speed of 280 r / min.

[0056] Example 2: This example discloses a high-ductility thin-layer repair concrete, which includes, by weight, 36 parts of dead-burned magnesium oxide, 12 parts of potassium dihydrogen phosphate, 10 parts of dried and qualified borax, 25 parts of metakaolin, 25 parts of fly ash, 10 parts of slag, and 1.2 parts of polyvinyl alcohol fiber.

[0057] The preparation method is as follows,

[0058] (1) Add the above-mentioned dead-burned magnesium oxide, potassium dihydrogen phosphate, dried and qualified borax, metakaolin, and polyvinyl alcohol fiber into a mixer, wherein the amount of polyvinyl alcohol fiber added is 40% of the total amount of polyvinyl alcohol fiber added, and at the same time, add the remaining polyvinyl alcohol fiber into water to wet it, and stir for 3 minutes at a speed of 140 r / min to form a solid gelling component;

[0059] (2) adding water soaked with polyvinyl alcohol fibers, wherein the ratio of the solid gelling component to water is 1:0.12, and the qualified conditions for the drying of the borax are: drying at 60-70° C. each time, ensuring that the drying time is between 30-40 hours, and the final three-time weight reduction rate of the borax is less than 0.1%; stirring for 1.5 minutes at a speed of 140 r / min, and gradually adding the slow-setting base material;

[0060] (3) Rapid stirring for 2 minutes at a speed of 280 r / min.

[0061] Example 3: This example discloses a high-ductility thin-layer repair concrete, which includes, by weight, 36 parts of dead-burned magnesium oxide, 12 parts of potassium dihydrogen phosphate, 10 parts of dried and qualified borax, 25 parts of metakaolin, 25 parts of fly ash, 10 parts of slag, 1.2 parts of polyvinyl alcohol fiber, and 5 parts of lightweight calcium powder.

[0062] The preparation method is as follows,

[0063] (1) adding the above-mentioned dead-burned magnesium oxide, potassium dihydrogen phosphate, dried qualified borax, metakaolin, polyvinyl alcohol fiber, and light calcium powder into a mixer, wherein the amount of polyvinyl alcohol fiber added is 40% of the total amount of polyvinyl alcohol fiber added, and the remaining polyvinyl alcohol fiber is added into water to moisten, wherein the conditions for the qualified drying of the borax are: drying at 60-70° C. each time, ensuring that the drying time is between 30-40 hours, and the final three-time weight reduction rate of the borax is less than 0.1%; stirring for 3 minutes at a speed of 140 r / min to form a solid gelling component;

[0064] (2) adding water soaked with polyvinyl alcohol fibers, wherein the ratio of the solid gelling component to water is 1:0.12, stirring for 1.5 minutes at a speed of 140 r / min, and gradually adding a slow-setting base material;

[0065] (3) Rapid stirring for 2 minutes at a speed of 280 r / min.

[0066] The high ductility thin layer repair concrete prepared in Example 1, Example 2 and Example 3 was tested and experimented.

[0067] Test items Example 1 Example 2 Example 3 Compressive strength(MPa) 115 121 127 Flexural strength(MPa) 15.9 16.7 16.9 Bond strength (MPa) 4.5 5.0 5.2 Antifreeze performance (F) 550 555 575 Gas content (%) 3 3 8

[0068] By comparing Example 1 and Example 2, it can be seen that by dispersing part of the polyvinyl alcohol fibers in advance and soaking the remaining part in water, the uniformity of dispersion can be improved and the moisture in the fibers is combined with potassium dihydrogen phosphate to provide a higher acidic environment to roughen its surface, thereby effectively improving the compression and flexural resistance of the repaired concrete and its bonding performance with the base cement.

[0069] By comparing Example 3 with Example 2, it can be seen that by adding lightweight calcium powder, bubbles are generated stably and evenly during the reaction process, which greatly increases the air content of the repaired concrete and significantly improves the antifreeze performance. 2+ Will replace Mg 2+ The PO4 that was not completely reacted in the early stage 3- A local reaction occurs, producing H + , H + The presence of accelerates the dissolution of dead-burned magnesium oxide, induces the late hydration of potassium magnesium phosphate cement, and increases its compressive strength.

[0070] Example 4: This example discloses a high-ductility thin-layer repair concrete, which includes, by weight, 30 parts of dead-burned magnesium oxide, 15 parts of potassium dihydrogen phosphate, 10 parts of dried and qualified borax, 25 parts of metakaolin, 25 parts of fly ash, 10 parts of slag, and 1.2 parts of polyvinyl alcohol fiber.

[0071] The preparation method thereof is completely the same as that of Example 2 except that the mix ratio of the repair concrete is different from that of Example 2.

[0072] Example 5: This example discloses a high-ductility thin-layer repair concrete, which includes, by weight, 36 parts of dead-burned magnesium oxide, 12 parts of potassium dihydrogen phosphate, 10 parts of untreated borax, 25 parts of metakaolin, 25 parts of fly ash, 10 parts of slag, and 1.2 parts of polyvinyl alcohol fiber.

[0073] The preparation method thereof is completely the same as that of Example 2 except that the mix ratio of the repair concrete is different from that of Example 2.

[0074] Example 6: This example discloses a high-ductility thin-layer repair concrete, which includes, by weight, 36 parts of dead-burned magnesium oxide, 12 parts of potassium dihydrogen phosphate, 10 parts of dried and qualified borax, 40 parts of metakaolin, 25 parts of fly ash, 10 parts of slag, and 1.2 parts of polyvinyl alcohol fiber.

[0075] The preparation method thereof is completely the same as that of Example 2 except that the mix ratio of the repair concrete is different from that of Example 2.

[0076] Example 7: This example discloses a high-ductility thin-layer repair concrete, which includes, by weight, 36 parts of dead-burned magnesium oxide, 12 parts of potassium dihydrogen phosphate, 10 parts of dried and qualified borax, 25 parts of metakaolin, 25 parts of fly ash, 10 parts of slag, and 3.5 parts of polyvinyl alcohol fiber.

[0077] The preparation method thereof is completely the same as that of Example 2 except that the mix ratio of the repair concrete is different from that of Example 2.

[0078] The high ductility thin layer repair concrete prepared in Example 4, Example 5, Example 6 and Example 7 were tested and experimented.

[0079]

[0080]

[0081] By comparing Example 4 with Example 2, it can be seen that the ratio of heavy-burned magnesium oxide and potassium dihydrogen phosphate is reduced, the early hydration reaction is too fast, a large amount of heat is released, the overheated environment makes the total amount of hydration products insufficient, and at the same time accelerates the coagulation speed, which has an adverse effect on construction. The compressive strength is also lower than the optional value. At the same time, there will be more unreacted MgO particles at the interface, resulting in reduced bonding strength.

[0082] By comparing Example 5 with Example 2, the borax content after water absorption is reduced, the corresponding retarding effect is also weakened, the setting time is shortened, and the unfavorable reaction is found. In addition, during stirring, a large amount of solid gelling components are found to adhere to the inner wall of the mixer, which needs to be cleaned after stirring, delaying the construction progress.

[0083] By comparing Example 6 with Example 2, it can be seen that as the amount of kaolin added increases, a large amount of kaolin will hinder the fluidity of the material due to its irregular shape, and the material performance is reduced to a certain extent. In addition, the content of heavy-burned magnesium oxide and potassium dihydrogen phosphate with excessive content is reduced, and the content of the required hydration product is reduced, which causes the material performance to decline, but it is within an acceptable range.

[0084] By comparing Example 7 with Example 2, it can be seen that as the amount of polyvinyl alcohol fiber added increases, the dispersion of the fiber decreases, and agglomeration occurs, which reduces the flexural and compressive properties of the material, but is within an acceptable range.

[0085] Comparative Example 1: This comparative example discloses a high-ductility thin-layer repair concrete, which comprises, by weight, 36 parts of dead-burned magnesium oxide, 12 parts of potassium dihydrogen phosphate, 10 parts of dried and qualified borax, 25 parts of fly ash, 10 parts of slag, and 1.2 parts of polyvinyl alcohol fiber.

[0086] The preparation method is as follows,

[0087] (1) adding the above-mentioned dead-burned magnesium oxide, potassium dihydrogen phosphate, dried borax and polyvinyl alcohol fiber into a mixer, wherein the conditions for the qualified drying of the borax are: drying at 60-70° C. each time, ensuring that the drying time is between 30-40 hours, and the final three-time weight reduction rate of the borax is less than 0.1%; stirring for 3 minutes at a speed of 140 r / min to form a solid gelling component;

[0088] (2) adding water, wherein the ratio of the solid gelling component to water is 1:0.16, stirring for 1.5 minutes at a speed of 140 r / min, and gradually adding a slow-setting base material;

[0089] (3) Rapid stirring for 2 minutes at a speed of 280 r / min.

[0090] Comparative Example 2: This comparative example discloses a high-ductility thin-layer repair concrete, which comprises, by weight, 36 parts of dead-burned magnesium oxide, 12 parts of potassium dihydrogen phosphate, 10 parts of dried and qualified borax, 25 parts of metakaolin, 25 parts of fly ash, and 10 parts of slag.

[0091] The preparation method is as follows,

[0092] (1) adding the above-mentioned dead-burned magnesium oxide, potassium dihydrogen phosphate, dried qualified borax and metakaolin into a mixer, wherein the conditions for the qualified drying of the borax are: drying at 60-70° C. each time, ensuring that the drying time is between 30-40 hours, and the final three-time weight reduction rate of the borax is less than 0.1%; stirring for 3 minutes at a speed of 140 r / min to form a solid gelling component;

[0093] (2) adding water, wherein the ratio of the solid gelling component to water is 1:0.16, stirring for 1.5 minutes at a speed of 140 r / min, and gradually adding a slow-setting base material;

[0094] (3) Rapid stirring for 2 minutes at a speed of 280 r / min.

[0095] The high ductility thin layer repair concrete prepared in Comparative Examples 1 and 2 was tested and experimented.

[0096]

[0097]

[0098] Compared with Example 2, Comparative Example 1 lacks the effect of filling cement gaps due to the absence of metakaolin, resulting in a decrease in cement density, a lack of viscous gelling substances produced by the reaction of metakaolin, and a decrease in bonding strength. This significantly reduces the compressive strength, bonding strength, and antifreeze properties of potassium magnesium phosphate cement, and the uneven dispersion of polyvinyl alcohol fibers also reduces the flexural strength.

[0099] By comparing Comparative Example 2 with Example 2, it can be seen that since no polyvinyl alcohol fiber is added, the bridging effect is missing in the concrete, causing the cracks to further expand. The lack of reinforcing and toughening components significantly reduces the flexural strength of potassium magnesium phosphate cement, and the compressive and bonding strengths are also reduced.

[0100] The above are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A high ductility thin layer repair concrete, characterized in that: The composition includes, by weight, 35-40 parts of dead-burned magnesium oxide, 5-15 parts of potassium dihydrogen phosphate, 5-20 parts of borax, 15-40 parts of metakaolin, 20-55 parts of retarding base material, 0.5-5 parts of polyvinyl alcohol fiber, and 3-8 parts of calcium increasing agent. The retarding base material is at least one of fly ash and slag, and the calcium increasing agent is light calcium powder, or a combination of light calcium powder and calcium oxide.

2. The high ductility thin layer repair concrete according to claim 1, characterized in that: The ratio of the dead-burned magnesium oxide to potassium dihydrogen phosphate is 2.8-3.2:

1.

3. The high ductility thin layer repair concrete according to claim 1, characterized in that: The weight proportion of the metakaolin is 20-35 parts.

4. The high ductility thin layer repair concrete according to claim 1, characterized in that: The weight proportion of the polyvinyl alcohol fiber is 0.8-1.5 parts.

5. The high ductility thin layer repair concrete according to claim 1, characterized in that: The length of the polyvinyl alcohol fiber is 5-8 mm.

6. The high ductility thin layer repair concrete according to claim 1, characterized in that: The weight proportions of the retarding base material are 15-40 parts of fly ash and 5-15 parts of slag.

7. A method for preparing a high-ductility thin-layer repair concrete, characterized in that: step: (1) Add the dead-burned magnesium oxide, potassium dihydrogen phosphate, borax, metakaolin, polyvinyl alcohol fiber, and calcium enhancer as described in any one of claims 1 to 6 into a mixer, and stir for 3 to 4 minutes at a speed of 140 r / min to form a solid gelling component, wherein the amount of polyvinyl alcohol fiber added is 30 to 50% of the total amount of polyvinyl alcohol fiber added, and add the remaining polyvinyl alcohol fiber into water to wet it; (2) adding water, wherein the water is water soaked with polyvinyl alcohol fibers, the ratio of the solid gelling component to water is 1:0.1-0.15, stirring for 1-2 minutes at a speed of 140 r / min, and gradually adding a slow-setting base material; (3) Stir rapidly for 1-2 minutes at a speed of 280 r / min.

8. The method for preparing a high-ductility thin-layer repair concrete according to claim 7, characterized in that: The borax is qualified dried borax, and the qualified dried borax condition is: drying at 60-70° C. each time, ensuring that the drying time is between 30-40 hours, and the final three-time mass reduction rate of the borax is less than 0.1%.